Mad world : an oral history of new wave artists and songs that defined the 1980s - Majewski, Lori; Bernstein, Jonathan (Abrams Image, 2014)
The authors provide an oral history that celebrates the New Wave music phenomenon of the 1980s via new interviews with some of the most notable artists of the period. Each chapter begins with a discussion of their most popular song but leads to stories of their history and place in the scene, ultimately painting a vivid picture of this colorful, idiosyncratic time.